SUSTAINABLE INNOVATION : OPTIMALISASI POTENSI BUAH JERUK DALAM MENCIPTAKAN KESEJAHTERAAN MASYARAKAT - Mu'awanah, Mu'awanah; Mu'awwanah, Uliyatul; Syarofi, Muhammad; S, Nashor Ade; Wibisana, Gunawan (AS-SUNNIYYAH, 2025)
The main goal of the SDGs is to address issues related to health and social welfare, which is one of the main problems for the Indonesia economy. Such as the phenomenon that occurred in Mundurejo Village, Jember Regency. The village, which is located in the west of Jember Regency, has abundant orange potential. However, unfortunately this potential is not accompanied by adequate knowledge to process it optimally. Therefore, activities are needed that are able to increase public understanding of citrus processing in order to increase selling value and usefulness, as well as support the welfare and economy of the village. This community service is packaged through training and strengthening cognition related to the importance of program sustainability. The method used in this service is the ABCD (Asset Based Community Development) method which is contained in 5 (five) steps of assistance, namely discovery, dream, design, define, and destiny. The target of this community service program is the people of Mundurejo village (especially orange farmers). Activities carried out include training on processing citrus fruits into mondy candies, processing orange waste (eco-enzyme) into dish soap and floor cleaning soap, marketing training, and the formation of PJM communities to support and monitor the sustainability of the program. Through this training, it is hoped that the people of Mundurejo village can make the most of the potential of oranges so that in turn they can improve village welfare and food independence for their people. This empowerment program aims to create significant sustainability, which not only increases the selling value of citrus fruits but also strengthens the local economy and supports the food welfare of the Mundurejo Village community as a whole.